2016
DOI: 10.1111/ina.12297
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation and dispersion of respiratory droplets from coughing

Abstract: Understanding how respiratory droplets become droplet nuclei and their dispersion is essential for understanding the mechanisms and control of disease transmission via droplet-borne and airborne routes. A theoretical model was developed to estimate the size of droplet nuclei and their dispersion as a function of the ambient humidity and droplet composition. The model-predicted dried droplet nuclei size was 32% of the original diameter, which agrees with the maximum residue size in the classic study by Duguid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
273
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(296 citation statements)
references
References 33 publications
5
273
0
2
Order By: Relevance
“…Similar results were also found by the numerical simulations of Chen et al and experimental works of Brohus and Nielsen . Liu et al studied the interpersonal exposure of exhaled droplets and droplet nuclei of two standing thermal manikins with a separation distance of 0.5‐3 m and suggested that the threshold distance of approximately 1.5 m distinguished the short‐range modes and the long‐range airborne route. The knowledge of this threshold distance is important for selecting the correct measures for controlling airborne transmission; however, very few studies have considered the impact of thermal stratification.…”
Section: Introductionsupporting
confidence: 80%
“…Similar results were also found by the numerical simulations of Chen et al and experimental works of Brohus and Nielsen . Liu et al studied the interpersonal exposure of exhaled droplets and droplet nuclei of two standing thermal manikins with a separation distance of 0.5‐3 m and suggested that the threshold distance of approximately 1.5 m distinguished the short‐range modes and the long‐range airborne route. The knowledge of this threshold distance is important for selecting the correct measures for controlling airborne transmission; however, very few studies have considered the impact of thermal stratification.…”
Section: Introductionsupporting
confidence: 80%
“…Therefore, targeting airborne pathogens could entail additional benefits, such as preventing or reducing the deposition of harmful microbes on secondary vehicles that include frequently touched environmental surfaces and also preventing or reducing their resuspension from these surfaces back into the air via a variety of indoor activities (Fig 1). 8,12,17,75,76 Further studies should investigate the role air decontamination may play in reducing the contamination of environmental surfaces and its combined impact on interrupting the risk of pathogen spread in both domestic and institutional settings.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The former is known as direct spray infection [2], in which relatively large (≥ 5 μm in diameter) droplets or droplet nuclei can be directly deposited on the nasal or oral mucosa of the new host. Short-range airborne exposure via smaller droplets or droplet nuclei is also important in close proximity infection [3]. Beyond 1–2 m, the exhaled air stream dissolves into the room airflow, and the pathogen-containing droplets or droplet nuclei are dispersed according to the global airflow in the room.…”
Section: Introductionmentioning
confidence: 99%